The effect of time of harvesting on seed storability and subsequent performance - Chin, Hoong Fong (International Society for Horticultural Science, 1981)
Longbean (V i g n a s e s qui p e d ali s) seeds of three different maturity i.e. harvested at 15, 20, 25 days after anthesis are compared at harvest and subsequently after one year storage. Immediately after harvesting, they differ significantly in moisture content. The moisture content of .immat ure seeds i.e. (15 days after anthesis) is 76.3 percent as compared to mature seeds (i.e. 25 days after anthesis) which is only 26.3 percent. On drying the immature seeds are lower in 1000 seed weight thar. the mature seeds. The percentage germination however does not differ significantly, but is lower for the immature seeds. After one year storage, the percentage germination is significantly lower for the immature seeds and highest for the mature seeds. The seeds after storage and when they are sown differ in their performance. The immature seeds produce less vigorous seedlings and plants, consequently they also produce lesser number of pods and lower yield. Hence immature seeds are low in seed quality, poorer in germination and do not store well.